Implementasi Perbup Mojokerto Nomor 2 Tahun 2024 dalam Pelaksanaan Pemilihan Perangkat Desa Jairowo Kecamatan Dawar Blandong - santosa santosa (Universitas Islam Majapahit, Indonesia, 2026)
Implementation of Mojokerto Regent Regulation Number 2 of 2024 concerning the guidelines for the implementation of Village Apparatus elections. This regulation has been amended twice from its original regulation, namely Mojokerto Regent Regulation number 8 of 2016, which then had the first amendment, namely Mojokerto Regent Regulation number 83 of 2018, after which there was a second amendment, namely Mojokerto Regent Regulation Number 2 of 2024. Research on the implementation of Mojokerto Regent Regulation Number 2 of 2024 concerning the second amendment to Mojokerto Regent Regulation number 8 of 2016 aims to describe the process of implementing the Jatirowo Village Apparatus election in 2026 based on the regulation. This research uses a descriptive qualitative method with a case study approach, data collection is carried out by data triangulation. The results of the study seen from the six-variable approach of Metter and Horn, namely policy objectives, resources, implementing agents, attitudes of implementers, communication between implementers and related institutions and the external environment that encourages the successful implementation of this Regent's Regulation show that the implementation of Mojokerto Regent Regulation Number 2 of 2024 concerning the second amendment to Mojokerto Regent Regulation Number 8 of 2016 concerning instructions for implementing the election of Village Apparatus in the election of Jatirowo Village Apparatus in 2026 is running well according to existing regulations, although there are obstacles in the implementation process.